Electrochemical investigation and thermodynamic assessment of the Mg-Pd system (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
This work presents the results of electromotive force measurements, by coulometric titration technique,  for liquid and solid Mg-Pd alloys with concentrations up to 0.70 mole fraction of Mg at 918 K. These measurements enabled verification of the range of homogeneity of the occurring phases and phase boundaries in the studied system.Based on the obtained results and other thermodynamic values found in the literature, the phase diagram of the Mg-Pd system was optimized using the CALPHAD method and ab initio calculations. The thermodynamic calculations successfully reproduced the phase diagram.
Keywords: Electromovie Force; Thermodynamic properties; Mg-Pd system; Phase diagram; Thermodynamic assessment